2017
DOI: 10.1136/bjophthalmol-2016-309134
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative aqueous humour flare values do not predict proliferative vitreoretinopathy in patients with rhegmatogenous retinal detachment

Abstract: Background/aims Patients with rhegmatogenous retinal detachment (RRD) who develop postoperative proliferative vitreoretinopathy (PVR) have been found to have higher preoperative laser flare values than patients with RRD who do not develop this complication. Measurement of laser flare has therefore been proposed as an objective, rapid and non-invasive method for identifying high-risk patients. The purpose of our study was to validate the use of preoperative flare values as a predictor of PVR risk in two additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
12
2
1
Order By: Relevance
“…In contrast to previous reports, we recently reported that the preoperative aqueous flare value is not a strong predictor for the development of PVR postoperatively (Mulder et al. ).…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to previous reports, we recently reported that the preoperative aqueous flare value is not a strong predictor for the development of PVR postoperatively (Mulder et al. ).…”
Section: Introductioncontrasting
confidence: 99%
“…Anterior chamber aqueous flarea surrogate marker for inflammation -has been proposed as a predictor for PVR in patients with a RRD (Schroder et al 2012;Hoerster et al 2013;Conart et al 2017). In contrast to previous reports, we recently reported that the preoperative aqueous flare value is not a strong predictor for the development of PVR postoperatively (Mulder et al 2017).…”
Section: Introductioncontrasting
confidence: 68%
See 3 more Smart Citations